Impact and Association of Anaemia Severity and Its Treatment With Quality of Life of Breast Cancer Patients in Malaysia - Ali Haider Mohammed; Fares Mohammed Saeed Muthanna; Bassam Abdul Rasool Hassan; Mahmathi Karuppannan; Abdulrasool M. Wayyes (Iraqi Journal of Pharmaceutical Sciences, 2022)
Anaemia is a crucial issue among cancer patients and need to be treated properly. High incidence of anaemia in patients with cancer have been associated with several physiological manifestations, leading to decreased quality of life (QOL).